The Competitive Edge: T6SS-Mediated Interference Competition by Vibrionaceae Across Marine Ecological Niches - Perla Jazmin Gonzalez Moreno; Michele K. Nishiguchi (Microorganisms)
Interference competition, wherein bacteria actively antagonize and damage their microbial neighbors, is a key ecological strategy governing microbial community structure and composition. To gain a competitive edge, bacteria can deploy a diverse array of antimicrobial weapons—ranging from diffusible toxins to contact-mediated systems in order to eliminate their bacterial rivals. Among Gram-negative bacteria, the type VI secretion system (T6SS) has emerged as a potent and sophisticated contact-dependent mechanism that enables the delivery of toxic cargo into neighboring cells, thereby promoting the colonization and dominance of a bacterial taxon within an ecological niche. In this review, we examine the ecological significance of T6SS-mediated interference competition by members of the Vibrionaceae family across a range of marine habitats that include free-living microbial communities and host-associated niches such as coral and squid symbioses. Additionally, we explore the ecological impact of T6SS-mediated competition in modulating biofilm community structure and promoting horizontal gene transfer within those complex microbial populations. Together, these insights underscore the ecological versatility of the T6SS and emphasize its role in driving antagonistic bacterial interactions and shaping microbial community dynamics within marine ecosystems.